Evaluation of the acceptability and validity of the Serious Illness Conversation Guide in oncology patients in South Africa - Burger, Henriette (Division of Family Medicine, 2025)
Background: Advance care planning (ACP) is the process through which a health care professional (HCP) guides a patient with a life-threatening illness to better understand their disease and to make value-concordant decisions for their future medical care including their end-of-life (EOL) care. The Serious Illness Conversation Guide (SICG, Ariadne Labs 2017) was developed and validated as a structured guide for HCPs when having ACP conversations with patients. Decision-making near the end of life is influenced by many factors including health status, socio-economic status, culture, ethnicity, and decisional control preferences. To our knowledge no study has explored the acceptability and validity of the SICG (Ariadne Labs) in cancer patients in South Africa (SA). Objectives: The aims of this study are to explore the local acceptability and validity of an internationally validated serious illness conversation guide for use in advance care planning conversations in South African patients with advanced cancer. Methods: A mixed-methods study design was used to explore the local acceptability and validity of the SICG using a survey and focus-group discussions (FGD) with healthcare professionals. In the quantitative survey each participant was asked to classify the local acceptability of each SICG prompt according to a 3-tiered system. Further survey questions assessed their practice settings, patterns of ACP, perceptions of cross-cultural acceptability of prompts, and the need for additional questions in the SICG. The FGD transcripts were qualitatively analysed using both inductive and deductive thematic analysis to reflect the research question as well as emerging themes. Results: Focus group discussions (FGD) were conducted with 17 healthcare workers during 2021. Analysis of the survey and FGD data suggests that several SICG prompt are not cross- culturally acceptable in their current state in the South African setting. Emerging factors influencing acceptability in the SA oncology context included poor illness understanding, the use of complex and incongruent language, health system limitations, the role of the family, and the role of belief systems and culture. Conclusion: The findings of this study can be used to adapt the Serious Illness Conversation Guide for the South African population to increase uptake of ACP and improve understanding of EOL care preferences for South Africans.